Pengaruh Harga Jual, Modal Sosial Dan Pengelolaan Keuangan Terhadap Pendapatan UMKM Di Wilayah Kecamatan Sambikerep Surabaya Barat - Resita Devi Cahyani; Wiwin Wahyuni (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of pricing strategy, social capital, and financial performance on the income of Micro, Small, and Medium Enterprises (MSMEs) in West Surabaya area. MSMEs play a vital role in the national economy but continue to face various challenges, such as inaccurate pricing, weak social capital, and poor financial record-keeping. This research adopts a quantitative approach using a survey method involving 95 MSME respondents. Data collection was carried out through a closed-ended questionnaire using a Likert scale. The independent variables include pricing strategy, social capital, and financial performance, while MSME income serves as the dependent variable. The data were analyzed using multiple linear regression to determine the partial and simultaneous effects of each variable. The findings of this study are expected to contribute theoretically to the development of MSME literature and provide practical recommendations for business actors and policymakers in enhancing income and sustainability of MSMEs.